Apical tissue resection in triangle operation during Whipple’s surgery - Maharjan, Dhiresh Kumar; Ghimire, Roshan; Limbu, Yugal; Regmee, Sujan; Parajuli, Anuj; Thapa, Prabin Bikram; Shrestha, Suman Kumar (Journal of Kathmandu Medical College, 2020)
Background: In pancreatic ductal adenocarcinoma, standardised concepts of radical surgical clearance have not been universally applied. Objectives: The main objective of this study is to reveal the status of circumferential resection margin of the apical tissue of the triangle namely the confluence of SMA and coeliac trunk in relation to circumferential resection margin of triangle tissue bounded by superior mesenteric artery, common hepatic artery and portal vein when performing the TRIANGLE operation. Methodology: This was a hospital-based cross-sectional study conducted at Kathmandu Medical College and Teaching Hospital, from September 2020 to December 2020. The study was done after ethical clearance from the Institutional Review Committee of Kathmandu Medical College. All consecutive patients who were subjected for Whipple’s operation for pancreatic head and uncinate process were included. Results: Fifteen patients underwent the “TRIANGLE” operation during a four months period. Median age of the patients was 65 ± 13.34 years (range 32–84 years). Medianpreoperative BMI 21.75± 2.5 (range: 18 to 26.7). Regarding histopathological results, an R0 resection was achieved in 9/15 patients. In nine patients,circumferential resection margin(CRM) of both the apical tissue and the rest of the triangle was negative. In the next three patients, the CRM of apical tissue was negative but the triangle tissue was positive whereas in the other three patients CRM of both the apical tissue and the triangle tissue were positive. Conclusion: This study emphasises the importance of inclusion of apical tissue dissection at the confluence of SMA and coeliac trunk in order to achieve R0 resection without significant short-term morbidity. However, a long-term follow is awaited.